Evolution of the acute uveitic phase in Vogt-Koyanagi-Harada Syndrome - Coelho Caiado , Gustavo; Crispim Dompieri, Rodrigo; Barcelos Daher, Valéria; de Castro Guimarães, Valeriana (Seven Editora, 2023)
Background: Vogt–Koyanagi–Harada (VKH) disease is an inflammatory and autoimmune condition characterized by panuveitis, serous retinal detachments and extraocular manifestations of the auditory, integumentary and central nervous systems. Patients with VKH can have good final outcomes if treated promptly with immunosuppressive agents and thus avoid complications. The purpose of this article is to report the evolution of the acute uveitis phase of VKH. Case Report: We report a case of a 58 years old women who presented to ophthalmology emergency room with a 10-day history of a severe headache and progressive low visual acuity in the left eye (LE). After seven days she developed low visual acuity (VA) in other eye and important tinnitus in her left ear. Ophthalmological examination showed best-corrected visual acuity (BCVA) of 20/200 in both eyes; direct and consensual motor reflexes decreased bilaterally; anterior chamber reaction with 2+ cells in both eyes. At Fundoscopy: bilaterally hyperemic optic discs, serous retinal detachment, retinal folds in the papillomacular bundle and Dalen-Fuchs nodules. Angiofluoresceinography (AGF) showed bilateral macular hyperfluorescence (pinpoints). Optical Coherence Tomography (OCT) showed bilateral subretinal fluid and loss of foveal depression. Oral prednisone 1,2mg/kg/day and topical dexamethasone were introduced with progressive tapering for 9 months with complete improvement in VA of the right eye and partial improvement in VA of the left eye. Conclusion: VKH can cause vision loss and blindness. Early diagnosis and adequate treatment with immuno-suppressive agents may halt disease progression and prevent recurrences and vision loss. DOI: 10.56238/pacfdnsv1-004